Parental Involvement in Autism Communication Interventions: A Qualitative Analysis - Widianti, Afra Afifah; Chamidah, Atien Nur (Proceeding of International Conference on Special Education in South East Asia Region, 2024)
The research investigates parental involvement in enhancing the communication skills of autistic children. Utilizing a qualitative research method with a case study approach examines 10 parents of verbally and non-verbally communicative autistic children. The data collection encompasses interviews and documentation techniques with the data analysis comprising data reduction, display, and conclusion followed by verification. The research findings indicate that parental contributions to communication skills enhance the implementation of mediation as a complement to therapy and specialized communication programs recommended by therapists and educators. Interventions are done based on assessments conducted in collaboration with therapists and educators. Intervention modalities, media, and methodologies are diversified to match the child’s needs but the lack of programmed sequences and schedules still emerges. Additionally, parental involvement extends to engaging other family members in the intervention process